AN INVESTIGATION OF ENGLISH FOR SPESIFIC PURPOSES PROGRAM AT A STATE ISLAMIC UNIVERSITY - Abdurohman, Mumu (2007)
The study aimed to investigate the implementation of teaching ESP at Islamic Education Department (PAI) of Faculty Tarbiyah and Teachers Training in UIN SGD Bandung. The research was guided by these three research questions: (1) how is the teaching of ESP conducted in Islamic Education Department of Faculty of Tarbiyah and Teachers Training? (2) what materials are provided for the students in the teaching of ESP in the research site? and (3) what are the students' needs in English learning? Are their needs relevant to the teaching English under ESP umbrella? The study was a case study. The data for this study were obtained through three instruments: 1) questionnaire for the students, 2) interview to the four lecturers, and 3) observation memo. These three instruments were used in order to get the 'soundness' of the obtained data.The study reveals that regarding the teaching materials used by the lecturers, the lecturer had already made good selections by carefully concerning on the linguistic content particularly on an adequate and appropriate description of the language characteristics of which the learners are required to handle. They also seem to be concerned much on the aspect of topics and themes related, the language and the content of the language that are not general. Regarding the teaching learning employed in the classroom, some phenomena indicate that learning-centered approach which is strongly advised for ESP class seems to fail to be applied. The teaching-learning process only covered the main activities in reading such as translation and comprehension or understanding the text. This evidence requires further investigation whether or not such activities assist students to construct their knowledge which is expected by the ESP rules in teaching. Concerning students' need in learning English, the students indicate their needs toward the use of the textbooks, handouts, the use of media for learning which are relevant to the their field of study. It is expected that the availability of these relevant media will help them to be able to dismiss the boredom during the teaching learning process, and to generate more active knowledge construction. Most of the time the research indicates that students' expectation in learning ESP tends to be more cultural and educational, and academic and occupational one than personal or individual.